ENDO PERIO LESION- A CASE REPORT - George, Priyanka Mariam (Journal of Medical Biomedical and Applied Sciences, 2017)
Endo Perio lesions are a common finding in the dental practice. Progression of an endodontic lesion, if allowed leads to periodontal involvement or vice versa. This is a case report on an endodontic lesion with periodontal involvement that has been treated by performing Root Canal Treatment (RCT) followed by flap surgery.